Susan Gets Ready for Church: A Monologue - MacKenzie, Edna I. (Salt Lake City, UT : Project Gutenberg, 2016)
"Susan Gets Ready for Church: A Monologue" by Edna I. MacKenzie is a comedic monologue likely written in the early 20th century. The book is a theatrical piece that captures the frantic morning routine of an ordinary girl named Susan as she prepares for church on a Sunday. The narrative unfolds through Susan's humorous and relatable thoughts and dialogues, providing insight into her character and the cultural context of the time. In the monologue, Susan's life is depicted as typical for a young girl in a domestic setting. She rushes through her morning preparations, expressing comedic frustrations with everything from her cold breakfast to finding her missing gloves. Throughout the piece, she interacts with her family members, showcasing a blend of sarcasm and everyday challenges. The humor shines through her commentary on the expectations of attending church and the pressures of appearances, especially concerning a new hat, which reflects societal values and adolescent concerns. The piece highlights the universal theme of balancing personal desires with family obligations, all delivered with a lighthearted touch. (This is an automatically generated summary.)
Release date is 2016-07-04
E-text prepared by Emmy, MWS, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Young women -- Drama; Monodramas; Conduct of life -- Drama